Serum Adiponectin is Associated with Adverse Outcomes of Asthma in Men but Not in Women - Sood, Akshay; Dominic, Elizabeth; Qualls, Clifford; Steffes, Michael W.; Thyagarajan, Bharat; Smith, Lewis J.; Lewis, Cora E.; Jacobs, David R. (Frontiers in Pharmacology, 2011)
BACKGROUND: Murine studies suggest a beneficial effect of systemic adiponectin on asthma. Our objective was to determine the association between serum adiponectin concentrations and asthma control/severity outcomes in men and women separately. METHODS: Cross-sectional and longitudinal analyses of data from years 10, 15, and 20 examinations of the prospective Coronary Artery Risk Development in Young Adults (CARDIA) study in the United States were performed. Asthma was defined by self-reported provider diagnosis at or prior to year 15 examination. Outcomes included presence of active disease, number of respiratory symptoms, and number of asthma medications; as well as longitudinal decline in absolute FEV1. Year 15 serum adiponectin concentration was the predictor variable. RESULTS: In a multivariable analysis of 411 eligible subjects, after adjusting for body mass index and covariates, higher serum adiponectin concentrations were associated with more frequent active disease (including more frequent use of any asthma medication) and greater number of respiratory symptoms and asthma medications among men but not among women with asthma (p for interactions between sex and adiponectin for all analyses < 0.05). CONCLUSIONS: Higher serum adiponectin concentrations may be independently associated with adverse clinical outcomes of asthma in men but not in women. If biological effect is confirmed in future studies, modification of systemic adiponectin concentrations may open up newer ways to treat asthma in men.